Multicenter Validation of Urinary CXCL9 as a Risk‐Stratifying Biomarker for Kidney Transplant Injury. Issue 10 (22nd August 2013) - Hricik, D. E.; Nickerson, P.; Formica, R. N.; Poggio, E. D.; Rush, D.; Newell, K. A.; Goebel, J.; Gibson, I. W.; Fairchild, R. L.; Riggs, M.; Spain, K.; Ikle, D.; et al.
Abstract: Noninvasive biomarkers are needed to assess immune risk and ultimately guide therapeutic decision‐making following kidney transplantation. A requisite step toward these goals is validation of markers that diagnose and/or predict relevant transplant endpoints. The Clinical Trials in Organ Transplantation‐01 protocol is a multicenter observational study of biomarkers in 280 adult and pediatric first kidney transplant recipients. We compared and validated urinary mRNAs and proteins as biomarkers to diagnose biopsy‐proven acute rejection (AR) and stratify patients into groups based on risk for developing AR or progressive renal dysfunction. Among markers tested for diagnosing AR, urinary CXCL9 mRNA (odds ratio [OR] 2.77, positive predictive value [PPV] 61.5%, negative predictive value [NPV] 83%) and CXCL9 protein (OR 3.40, PPV 67.6%, NPV 92%) were the most robust. Low urinary CXCL9 protein in 6‐month posttransplant urines obtained from stable allograft recipients classified individuals least likely to develop future AR or a decrement in estimated glomerular filtration rate between 6 and 24 months (92.5–99.3% NPV). Our results support using urinary CXCL9 for clinical decision‐making following kidney transplantation. In the context of acute dysfunction, low values can rule out infectious/immunological causes of injury. Absent urinary CXCL9 at 6 months posttransplant defines a subgroup at low risk for incipient immune injury. Abstract : In this multicenter observational study of 280 kidney transplant recipients, the investigators determine that, among multiple urinary mRNA and protein biomarkers studied, results of urinary CXCL9 protein ELISAs best identify patients at the lowest risk for ongoing and/or incipient immune‐mediated allograft injury. See editorial by Srinivas and Kaplan on page 2519.